Conserved Residues Lys57 and Lys401 of Protein Disulfide Isomerase Maintain an Active Site Conformation for Optimal Activity: Implications for Post-Translational Regulation - Caba, Cody; Ali Khan, Hyder; Auld, Janeen; Ushioda, Ryo; Araki, Kazutaka; Nagata, Kazuhiro; Mutus, Bulent (Frontiers in Molecular Biosciences, 2018)
Despite its study since the 1960's, very little is known about the post-translational regulation of the multiple catalytic activities performed by protein disulfide isomerase (PDI), the primary protein folding catalyst of the cell. This work identifies a functional role for the highly conserved CxxC-flanking residues Lys57 and Lys401 of human PDI in vitro. Mutagenesis studies have revealed these residues as modulating the oxidoreductase activity of PDI in a pH-dependent manner. Non-conservative amino acid substitutions resulted in enzyme variants upwards of 7-fold less efficient. This attenuated activity was found to translate into a 2-fold decrease of the rate of electron shuttling between PDI and ERO1α suggesting a functional significance to oxidative protein folding. The possibility of lysine acetylation at residues Lys57 and Lys401 was then assessed by in vitro treatment using acetylsalicylic acid (aspirin). A total of 28 acetyllysine residues were identified, including acLys57 and acLys401. The kinetic behavior of acetylated PDI was nearly identical to that obtained with a K57/401Q double substitution providing a strong indication that acetylation of the active site-flanking lysine residues can act to reversibly modulate PDI activity.